THE EFFECT OF CAPITAL ADEQUACY, OPERATIONAL EFFICIENCY, AND THIRD-PARTY FUNDS ON PROFITABILITY IN SHARIA COMMERCIAL BANKS IN INDONESIA - Putri Diah Salsabillah; Haqiqi Rafsanjani; Tiara Anindya Virana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), and Third Party Funds (DPK) on Return on Assets (ROA) in Sharia Commercial Banks in Indonesia. This study uses an associative quantitative approach with secondary data on the monthly time series for the 2018–2024 period sourced from the Financial Services Authority (OJK). The analysis method used is the Vector Error Correction Model (VECM), with stages of testing stationery, optimal lag, VAR stability, Granger causality, and Johansen cointegration, and equipped with Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) analysis. The results of the study showed that some variables were not stationary at the level level, but all variables were stationary at the first difference. The Johansen cointegration test showed that there was a long-term relationship between variables, so the VECM model was feasible. The estimated results show that CAR does not have a significant effect on ROA in the short term. BOPO has a negative and significant effect on ROA in the short term, while deposits also have a negative and significant effect on ROA. The IRF results show that the ROA response to shock is temporary, while the FEVD shows that the variation in ROA is more explained by the ROA shock itself. This finding indicates that the profitability of Sharia Commercial Banks is more influenced by operational efficiency and optimization of fund management than capital adequacy alone.